Răspuns:
Explicație pas cu pas:
(2 ; -2)
a)
{4x+3 = 5-3y
{x-y = 0 Verificam daca x = 2 ; y = -2 este solutie :
{4·2+3 = 11 = 5-3·(-2) = 5+6 = 11 , corect
{2-(-2) = 4 ≠ 0 =>
x = 2 ; y = -2 nu este solutie a sistemului
b)
{3x+3y = 0
{5x-y = 12
{3·2 + 3·(-2) = 6-6 = 0 ; corect
{5·2-(-2) = 10+2 = 12 , corect =>
x = 2 ; y = -2 este solutie a sistemului
c)
{5x+y = 7
{3x-y = 8
{5·2 +(-2) = 10-2 = 8 ≠ 7 =>
x = 2 ; y = -2 nu este solutie a sistemului
d)
{7x-y = 16
{3x+2y = 2
{7·2-(-2) = 14+2 = 16 , corect
{3·2+2·(-2) = 6-4 = 2 , corect =>
x = 2 ; y = -2 este solutie a sistemului